It's not what you do it's the way that it's measured: quality assessment of minor ailment management in community pharmacies. (28th September 2016) - Inch, Jackie; Porteous, Terry; Maskrey, Vivienne; Blyth, Annie; Burr, Jackie; Cleland, Jennifer; Wright, David J.; Holland, Richard; Bond, Christine M.; Watson, Margaret C.
Abstract: Background: Effective management of minor ailments in community pharmacies could reduce the burden on alternative high‐cost services (general practices, Emergency Departments). Evidence is needed regarding the appropriateness of management of these conditions in community pharmacies. Objective: To explore the appropriateness of minor ailment management in community pharmacies. Setting: Prospective, observational study of simulated patient (SP) visits to community pharmacies in Grampian (Scotland) and East Anglia (England). Method: Eighteen pharmacies (nine per centre) were recruited within a 25‐mile radius of Aberdeen or Norwich. Consultations for four minor ailments were evaluated: back pain; vomiting/diarrhoea; sore throat; and eye discomfort. Each pharmacy received one SP visit per ailment (four visits/pharmacy; 72 visits total). Visits were audio‐recorded and SPs completed a data collection form immediately after each visit. Primary Outcome Measure: Each SP consultation was assessed for appropriateness against product licence, practice guidelines and study‐specific consensus standards developed by a multi‐disciplinary consensus panel. Results: Evaluable data were available for 68/72 (94.4%) visits. Most (96%) visits resulted in the sale of a product; advice alone was the outcome of three visits. All product sales complied with the product licence, 52 (76%) visits complied with practice guidelines and seven visits achieved a 'basic' standard according to the consensus standard. Conclusion: Appropriateness of care varied according to the standard used. Pharmacy‐specific quality standards are needed which are realistic and relevant to the pharmacy context and which reflect legal and clinical guidelines to promote the safe and effective management of minor ailments in this setting.